Ring Y chromosome: molecular characterization by DNA probes - Pohlschmidt, Manfred; Rappold, Gudrun; Krause, M.; Ahlert, Dorothee; Hosenfeld, Detlev Joachim; Weissenbach, Jean; Gal, Andreas (Cytogenetics and cell genetics, 1991)
A young male with a karyotype of 46, X,+mar is described. Physical mapping of the marker chromosome by using Y-specific single-copy or moderately repeated DNA sequences as molecular probes showed that, in addition to the heterochromatic part of the Yq, a considerable portion of the euchromatin in both Yp and Yq had been lost. These findings suggest that the marker chromosome is a ring Y, for the generally accepted model of ring formation implies breakages in both chromosome arms. The clinical features of the patient correlated well with the phenotypic changes expected from the loss of genetic material from the Y.